Concept Of The Mosque As An Education Means Faith And The End Of Children In The Modern Era - Nurhadi Nurhadi (Nazhruna: Jurnal Pendidikan Islam, 2019)
In this Modern era, mosques are very grand and luxurious as a form of development of Islamic civilization. Not only for ubudiyah, the mosque is one of the non-formal educational facilities for the Islamic community. In order for the mosque to function properly in Islamic law. So it needs an applicative and simple theory, according to the author, so that mosques can become educational facilities for children, it needs to be arranged in a systematic and directed manner, namely: 1). Looking for prospective husband and wife at the mosque. 2). Ta'aruf at the mosque. 3). Marriage contract at the mosque. 4). Pregnancy Children always go to the mosque. 5). Born Son in Azankan like Azan at the Mosque. 6). Since toddlers and children always learn Koran at the mosque. 7). Since Children and Mumayiz always pray at the mosque. 8). After Baligh Teach Stay at the Mosque. 9). After Adult, look for a diligent soul mate to the mosque. If the nine points above are implemented, then mosques will naturally become a mecca for the education of Islamic children. So the purpose of education is to make insane kamil who are devoted and have moral character.